1994
DOI: 10.1002/jemt.1070270207
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the cytoskeleton during mammalian oogenesis

Abstract: Mammalian oogenesis is a process which requires a variety of changes in the structure and function of the specialized female germ cell. Evidence suggests that the cytoskeleton may mediate several of these structural and functional changes. In this review we evaluate what is known of cytoskeletal function during oogenesis, with emphasis on specialized cytoskeletal features in mammals. Existing investigations suggest that the oocyte, as a highly specialized cell, contains unique cytoskeletal elements which exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Additionally, phosphate can affect the critical concentration of actin necessary for assembly of actin microfilaments (Rickard and Shetterline, 1986) and stabilize microtubules (Carlier et al, 1988) in other cell types. It is unknown whether intermediate filament proteins are involved with organization of the mitochondria, although their presence in hamster preimplantation embryos has been described (Gallicano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, phosphate can affect the critical concentration of actin necessary for assembly of actin microfilaments (Rickard and Shetterline, 1986) and stabilize microtubules (Carlier et al, 1988) in other cell types. It is unknown whether intermediate filament proteins are involved with organization of the mitochondria, although their presence in hamster preimplantation embryos has been described (Gallicano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…(79)(80)(81)(82), the majority of investigations have shown that the physiological localization of intermediate filaments is in a highly crosslinked network, which is completely coated with a layer of one or more proteins. Based on numerous ultrastructural observations the orientation of crosslinked filaments and protein coat give these cytoskeletal structures a sheet-like appearance, hence they have been termed "cytoskeletal sheets" (29,31,83,84).…”
Section: The Cytoskeleton During Fertilizationmentioning
confidence: 99%
“…The evidence is strong as eggs and early embryos from several mammalian species were subjected to numerous different biochemical and ultrastructural methodologies. One of the first observations made from employing these approaches was the finding of two types of sheets, one with a fibrous composition and the other a more planar composition (29,77,83). Each species examined contained only one type of sheet.…”
Section: The Cytoskeleton During Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation